Echocardiographic detection of free-floating thrombus in left ventricle during coronary artery bypass grafting - Vaggar, Jagadeesh N. (Ann Card Anaesth, 2015)
We report an incident of detection of a free-floating thrombus in the left ventricle (LV) using intraoperative two-dimensional (2D) and three-dimensional (3D) transesophageal echocardiography (TEE) during proximal coronary artery bypass graft anastomosis. A 58-year-old man presented to us with a 6-month history of chest pain without any history suggestive of myocardial infarction or transient ischemic attacks. His preoperative echocardiography revealed the systolic dysfunction of LV, mild hypokinesia of basal and mid-anterior wall, and the absence of an aneurysm. He was scheduled for on-pump coronary artery bypass surgery. On intraoperative TEE before establishing cardiopulmonary bypass (CPB), a small immobile mass was found attached to LV apical area. After completion of distal coronary artery grafting, when the aortic cross-clamp was removed, the heart was filled partially and beating spontaneously. TEE examination using 2D mode revealed a free-floating mass in the LV, which was suspected to be a thrombus. Additional navigation using biplane and 3D modes confirmed the presence of the thrombus and distinguished it from papillary muscles and artifact. The surgeon opened the left atrium after re-establishing electromechanical quiescence and removed a thrombus measuring 1.5 cm × 1 cm from the LV. The LV mass in the apical region was no longer seen after discontinuation of CPB. Accurate TEE-detection and timely removal of the thrombus averted disastrous embolic complications. Intraoperative 2D and recent biplane and 3D echocardiography modes are useful monitoring tools during the conduct of CPB.